TURKEY SAMPLE: THE RELATIONSHIP BETWEEN MEN’S SATISFACTION WITH LOVE LIFE AND SEXUAL COMPULSIVITY - AYAR, Duygu; İÇEL, Sema (Göbeklitepe Medical Science Journal, 2021)
Aim: This study was conducted to determine the relationship between men’s satisfaction with love life and sexual compulsivity. Method: The descriptive and cross-sectional study was conducted with 272 individuals. Data were collected with the Personal Information Form, the Satisfaction with Love Life Scale, and the Sexual Compulsivity Scale. ANOVA, Mann-Whitney U, Kruskal Wallis, correlation, and regression tests were used to evaluate the data. The ethics committee permission was obtained to conduct the research. Results: Men’s Satisfaction with Love Life total mean score was calculated as 19.17±8.41, and the total mean score of the Sexual Compulsivity Scale was determined as 19.31±7.85. A negative and weak correlation was determined between the Satisfaction with Love Life Scale and the Sexual Compulsivity Scale. Conclusion: It was determined that as men’s satisfaction with love life increased, their sexual compulsivity levels decreased.